Emotional recognition across the adult lifespan: Effects of age, sex, cognitive empathy, alexithymia traits, and amygdala subnuclei volumes. Issue 3 (7th December 2022) - Malykhin, Nikolai; Pietrasik, Wojciech; Aghamohammadi‐Sereshki, Arash; Ngan Hoang, Kim; Fujiwara, Esther; Olsen, Fraser
Abstract: The ability to recognize others' emotions is vital to everyday life. The goal of this study was to assess which emotions show age‐related decline in recognition accuracy of facial emotional expressions across the entire adult lifespan and how this process is related to cognitive empathy (Theory of Mind [ToM]), alexithymia traits, and amygdala subnuclei volumes in a large cohort of healthy individuals. We recruited 140 healthy participants 18–85 years old. Facial affect processing was assessed with the Penn Emotion Recognition task (ER40) that contains images of the five basic emotions: Neutral, Happy, Sad, Angry, and Fearful. Structural magnetic resonance imaging (MRI) datasets were acquired on a 4.7T MRI system. Structural equation modeling was used to test the relationship between studied variables. We found that while both sexes demonstrated age‐related reduction in recognition of happy emotions and preserved recognition of sadness, male participants showed age‐related reduction in recognition of fear, while in female participants, age‐related decline was linked to recognition of neutral and angry facial expressions. In both sexes, accurate recognition of sadness negatively correlated with alexithymia traits. On the other hand, better ToM capabilities in male participants were associated with improvement in recognition of positive and neutral emotions. Finally, none of the observed age‐related reductions in emotional recognition were related to amygdala and its subnuclei volumes. In contrast, both global volume of amygdala and its cortical and centromedial subnuclei had significant direct effects on recognition of sad images. Abstract : This multidimensional assessment of emotion recognition in healthy adults suggested that age could affect emotion recognition differently in men and women, and these age‐related differences were not mediated by amygdala volume. Our results also indicated that emotion‐processing factors are not independent of personality traits and general cognition.